2022
DOI: 10.3390/cells11132014
|View full text |Cite
|
Sign up to set email alerts
|

The E3 Ubiquitin Ligase Peli1 Deficiency Promotes Atherosclerosis Progression

Abstract: Background: Atherosclerosis is a chronic inflammatory vascular disease and the main cause of death and morbidity. Emerging evidence suggests that ubiquitination plays an important role in the pathogenesis of atherosclerosis including control of vascular inflammation, vascular smooth muscle cell (VSMC) function and atherosclerotic plaque stability. Peli1 a type of E3 ubiquitin ligase has emerged as a critical regulator of innate and adaptive immunity, however, its role in atherosclerosis remains to be elucidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Signaling pathways include immune system [54], metabolism of lipids [55], phospholipid metabolism [56] and disease [57] plays an important role in CAD. DOCK4 [58], CEACAM1 [59], STAT1 [60], ARG1 [61], TLR4 [62], ADAM9 [63], VNN1 [64], ABCA1 [65], STAT2 [66], TLR5 [67], PTGS2 [68], RNF213 [69], ZDHHC17 [70], JAK2 [71], TLR8 [72], NOTCH2 [73], PDGFC (platelet derived growth factor C) [74], CMPK2 [75], TLR2 [76], CYP1B1 [77], CCR1 [78], HDAC9 [79], IL1RN [80], GCH1 [81], LYST (lysosomal trafficking regulator) [82], PELI1 [83], EGR1 [84], SNX10 [85], CA2 [86], ZEB2 [87], HIF1A [88], PLA2G7 [89], CCR2 [90], GAB1 [91], IRAK3 [92], LDLR (low density lipoprotein receptor) [93], TLR6 [94], SIRT1 [95], NOD2 [96], ATP10D [97], ELOVL6 [98], VCAN (versican) [99], TET2 [100], TET3 [101], ZBTB20 [102], HS3ST1 [103], PF4 [104], DNAJC2 [105], NFIA (nuclear factor I A) [106], CCR7 [107], PRDX2 [108], ADK (adenosine kinase) [109], TCF7 [110], LGALS3 [111], OLFM2 [112], HDAC11 [113] and ARPC1B [114] are significantly related to the atherosclerosis. Studies have revealed that KCNJ2 [115], TLR4 [116], JAK2 [117], TLR2 [118], EGR1 [119], GAB1 [120], ZBTB11 [121], BIN1 [122], TCF4 [123], PPP1R13L [124], TRPM4 [125], LGALS3 [126] and SNTA1 [127] plays a key role in cardiac arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Signaling pathways include immune system [54], metabolism of lipids [55], phospholipid metabolism [56] and disease [57] plays an important role in CAD. DOCK4 [58], CEACAM1 [59], STAT1 [60], ARG1 [61], TLR4 [62], ADAM9 [63], VNN1 [64], ABCA1 [65], STAT2 [66], TLR5 [67], PTGS2 [68], RNF213 [69], ZDHHC17 [70], JAK2 [71], TLR8 [72], NOTCH2 [73], PDGFC (platelet derived growth factor C) [74], CMPK2 [75], TLR2 [76], CYP1B1 [77], CCR1 [78], HDAC9 [79], IL1RN [80], GCH1 [81], LYST (lysosomal trafficking regulator) [82], PELI1 [83], EGR1 [84], SNX10 [85], CA2 [86], ZEB2 [87], HIF1A [88], PLA2G7 [89], CCR2 [90], GAB1 [91], IRAK3 [92], LDLR (low density lipoprotein receptor) [93], TLR6 [94], SIRT1 [95], NOD2 [96], ATP10D [97], ELOVL6 [98], VCAN (versican) [99], TET2 [100], TET3 [101], ZBTB20 [102], HS3ST1 [103], PF4 [104], DNAJC2 [105], NFIA (nuclear factor I A) [106], CCR7 [107], PRDX2 [108], ADK (adenosine kinase) [109], TCF7 [110], LGALS3 [111], OLFM2 [112], HDAC11 [113] and ARPC1B [114] are significantly related to the atherosclerosis. Studies have revealed that KCNJ2 [115], TLR4 [116], JAK2 [117], TLR2 [118], EGR1 [119], GAB1 [120], ZBTB11 [121], BIN1 [122], TCF4 [123], PPP1R13L [124], TRPM4 [125], LGALS3 [126] and SNTA1 [127] plays a key role in cardiac arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…The TF-hub gene regulatory network included 535 (TF: 181; gene: 354) nodes and 9293 interactions (Fig 6). We discovered that that EGR1 was targeted by 53 TFs (ex; LMO2); DDX5 was targeted by 51 TFs (ex; MYCN); NCOA3 was targeted by 48 TFs (ex; SIN3B); STAT1 was targeted by 42 TFs (ex; IRF8); HIF1A was targeted by 40 TFs (ex; GATA1); RPS14 was targeted by 45 TFs (ex; RCOR3); RPL3 was targeted by 44 TFs (ex; DMRT1); RPS19 was targeted by 42 TFs (ex; GCH1 [81], LYST (lysosomal trafficking regulator) [82], PELI1 [83], EGR1 [84], SNX10 [85], CA2 [86], ZEB2 [87], HIF1A [88], PLA2G7 [89] [105], NFIA (nuclear factor I A) [106], CCR7 [107], PRDX2 [108], ADK (adenosine kinase) [109], TCF7 [110], LGALS3 [111], OLFM2 [112], HDAC11 [113] and ARPC1B [114] are significantly related to the atherosclerosis. Studies have revealed that KCNJ2 [115], TLR4 [116], JAK2 [117], TLR2 [118], EGR1 [119], GAB1 [120], ZBTB11 [121], BIN1 [122], TCF4 [123], PPP1R13L [124], TRPM4 [125], LGALS3 [126] and SNTA1 [127] plays a key role in cardiac arrhythmia.…”
Section: Construction Of the Tf-hub Gene Regulatory Networkmentioning
confidence: 99%
“…Peli1, as a ubiquitin ligase, acts as key roles in the pathogenesis of in ammatory diseases, including AS [15]. Burger et al demonstrated that Peli1 de ciency accelerated AS progression by promoting VSMCs foam cells formation [15], revealing the protective role of Peli1 in AS. Herein, we identi ed YB-1 as the functional target of Peli1 in regulating AS progression.…”
Section: Discussionmentioning
confidence: 99%
“…E3 ubiquitin ligase Pellino 1 (Peli1) is an E3 ubiquitination ligase, which can mediate the ubiquitination of downstream targets and then regulate immune responses [14]. Interestingly, Peli1 functions in regulating systemic and local vascular in ammation, and Peli1 de ciency facilitates foam cells formation to promote AS progression [15]. Herein, by using bioinformatics prediction, it was found that YB1 is the potential substrate of Peli1.…”
Section: Introductionmentioning
confidence: 99%
“…57 The data indicate that decreased HRD1 expression in ECs may be related to the pathogenesis of atherosclerosis and modulation of HRD1 expression could represent an effective therapeutic target for atherosclerosis. Considering the pathological changes of multiple cell types during atherosclerosis, the role of E3 ubiquitin ligases in the regulation of other cell types, including foam cells and vascular smooth muscle cells, 58,59 could not be ignored. In addition, the combined intervention of E3 ubiquitin ligase in different cell types may be a potential treatment for preventing or attenuating atherosclerosis.…”
Section: Atherosclerosismentioning
confidence: 99%